2013
DOI: 10.1007/s12291-013-0345-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Stress Induced TREM-1 and Inflammatory Chemokines in Human Peripheral Blood Mononuclear Cells

Abstract: Hypoxia is a condition of low pO 2 , which creates a unique microenvironment affecting cell phenotype and subsequent immune response generation. Little is known about the impact of hypoxia on the phenotypic expression of NK cell, TREM-1, TLR-4 and inflammatory chemokines. In the present study we have determined the frequency of peripheral blood populations of CD16/CD56 (NK Cells) expressing cells, presence of activation marker CD354 (TREM-1), Toll like receptor (CD 284) on the cell surface and chemokines IL-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Indeed hypoxia exposure whether, in vitro or in vivo, is associated with rise in inflammatory markers. However, in the previous studies, as also quoted in the article by the authors, the duration of hypoxia exposure varied from 16 to 72 h [2][3][4][5] On the contrary, in the present study duration of simulated hypoxia of 4500 m was only 30 min. It remains obscure that those changes seen in the chemokines are actually the result of hypoxia induced inflammation or otherwise.…”
Section: To the Editorcontrasting
confidence: 50%
“…Indeed hypoxia exposure whether, in vitro or in vivo, is associated with rise in inflammatory markers. However, in the previous studies, as also quoted in the article by the authors, the duration of hypoxia exposure varied from 16 to 72 h [2][3][4][5] On the contrary, in the present study duration of simulated hypoxia of 4500 m was only 30 min. It remains obscure that those changes seen in the chemokines are actually the result of hypoxia induced inflammation or otherwise.…”
Section: To the Editorcontrasting
confidence: 50%
“…It has also been demonstrated that that Nickel and Cobalt ions can induce IL-8 production via human TLR4 activation [ 17 ; 55 ]. However, it has also been reported that hypoxia can result in up-regulation of both TLR4 expression and IL-8 production and thus, whether this TLR4 induced IL-8 is a primary or secondary effect of Cobalt is not known [ 56 ; 57 ]. Therefore, it is possible that previous investigations of observed cobalt induced IL-8 may have been due to Cobalt toxicity responses eliciting a hypoxia state and increased endogenous alarmins/DAMPs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated HIF1α activity eventually resulted in elevated IL-8 expression. TREM1 protein expression and IL-8 secretion were both previously reported to be increased under hypoxic conditions ( 68 ). We could show that NiSO 4 -treated MoDCs also induced TREM1 signaling as well as IL-8 secretion.…”
Section: Discussionmentioning
confidence: 82%